OMAH TANI AS A PRACTICE OF INTER-RELIGIOUS DIALOGUE BASED ON DIA-PRAXIS AND DECOLONIZATION - Amriani, Nita; Yogesi, Novitama Putri; Alfian, Andi (Al-Qalam, 2025)
Interfaith dialogue in Indonesia is generally framed as a formal religious forum oriented toward theological consensus, which may limit more comprehensive engagement across different social contexts. This approach often to overlooks the dynamics of interreligious praxis that grow organically in social spaces, particularly in the context of agrarian movements and struggles for structural justice. This study aims to examine the Omah Tani community in Batang, Central Java, as a manifestation of interfaith dialogue rooted in agrarian solidarity and collective action. Using a qualitative case study design, data is collected through in-depth interviews, observations, and documentation and analysis. The analysis is conducted thematically, drawing on the theoretical frameworks of dia-praxis and the decolonization of religion, to explore how expressions of faith are realized in social actions that transcend doctrinal and institutional boundaries. The research findings indicate that interfaith interaction within the Omah Tani community takes place through collective work in land management, agrarian policy advocacy, and interreligious spiritual practices. This form of engagement creates a participatory and horizontal dialogue space, where solidarity becomes the foundation of inclusive and transformative religiosity. This research offers a conceptual contribution to expanding the paradigm of interfaith dialogue, from one that previously focused solely on theological discussions among elites to one realized through collective action. By examining Omah Tani’s experience, this research demonstrates that faith or religion is not merely an individual expression but also a collective force in the struggle for justice. The case of Omah Tani demonstrates that interfaith dialogue can transcend exclusivity and “colonial” perspectives, growing in a collaborative space grounded in solidarity and commitment to vulnerable groups.